Unraveling the Induction of Phytoene Synthase 2 Expression by Salt Stress and Abscisic Acid in Daucus Carota - Contreras-Arredondo, R (Oxford University Press, 2018)
Phytoene synthase (PSY) is the first committed enzyme of the carotenoid biosynthesis pathway and the most important point of regulation. Carotenoids are precursors of abscisic acid (ABA), which mediates abiotic stress tolerance responses in plants. ABA activates the synthesis of its own precursors through induction of PSY expression. Carrot, a species that accumulates very high amounts of carotenoids in its reserve root, has two PSY paralog genes that are expressed differentially in the root. Here, we determined that DcPSY2 expression is induced by salt stress and ABA. A DcPSY2 promoter fragment was obtained and characterized. Bioinformatic analysis showed the presence of three ABA responsive elements (ABREs). Through overexpressing pPSY2:GFP in Nicotiana tabacum we determined that all three ABREs are necessary for the ABA response. In the carrot transcriptome, we identified three ABRE binding protein (DcAREB) transcription factor candidates that localized in the nucleus, but only one, DcAREB3, was induced under ABA treatment in carrot roots. We found that AREB transcription factors bind to the carrot DcPSY2 promoter and transactivate the expression of reporter genes. We conclude that DcPSY2 is involved in ABA-mediated salt stress tolerance in carrot through the binding of AREB transcription factors to its promoter. © The Author(s) 2018. Published by Oxford University Press on behalf of the Society for Experimental Biology.